Impact of artificial intelligence (AI) system implementation in the construction industry: Case study of Klang valley - Chan, Huey Min (2023)
The implementation of Artificial Intelligence (AI) systems in the construction industry has been a topic of interest in recent years due to its potential to improve efficiency, productivity, and safety. This study aims to investigate the impact of AI system implementation in the construction industry, using Klang Valley as a case study. The study will explore the current use of AI systems in the industry, identify the challenges faced by construction companies during implementation, and evaluate the impact of AI systems on the industry's productivity, cost, and safety and security. The study will be conducted through undergo a survey with industry experts and the employees in construction industry. The findings of this study will provide insights into the benefits and limitations of AI systems in the construction industry, which can be used to guide future implementation and policy decisions.